A generic cyclist model for aerodynamic investigation: Design, geometry & first aerodynamic analysis of a male time-trial and sprint model - Terra, W.; Brown, C.; Vloemans, S.; van der Waals, M.; Sciacchitano, A.; Burton, D.; Thompson, M. C.; Huysmans, T. (Journal of Wind Engineering and Industrial Aerodynamics, 2024)
Research in cycling aerodynamics is performed using mannequins of different geometries, which are usually not shared, thus hampering the advancement of our understanding of the flow around a rider on the bike. The primary outcome of this work is to introduce and openly share two anthropometrically realistic generic cyclist models, one in time-trial and one in sprint position. These two models are obtained by averaging the scans of 14 male elite cyclists. The average cyclist geometries are published and openly accessible, making them unique in the field of cycling aerodynamic research. The second objective of this work is to better understand how the difference between the sprint and time-trial position affects the velocity and vortex topology in the wake of a cyclist and, in turn, the aerodynamic drag. Robotic volumetric particle image velocimetry measures the time-average velocity for each mannequin within a wind tunnel. One meter downstream of the lower back, the wakes of the two mannequins are dominated by strong hip/thigh streamwise counter-rotating vortices, which induce a downwash behind the riders` backs. The strength of these vortices downstream of the sprint model is significantly larger than that of the vortices of the mannequin in the time-trial position. The same holds for a secondary vortex pair that originates from the upper arms and hips. In addition to the vortex strength, the aerodynamic drag area of the sprint model exceeds that of the time-trial model. Hence, it is presumed that stronger vortices relate to higher aerodynamic drag. In contrast to the drag area, the drag coefficient of the two models is the same. Further research is necessary to understand the relation between the cyclist position, the flow topology and the drag coefficient. Finally, the flow around the time-trial model is described in further detail to understand the origin of the different vortex structures. Through comparison to the literature, a vortex topology classification is postulated for the mid-wake and upper-wake. The arm spacing and shoulder width play a critical role in the development of this vortex system.